2018
DOI: 10.1115/1.4041245
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Elastic–Plastic Cutting Model for Predicting Grain Depth-of-Cut in Ultrafine Grinding of Silicon Wafer

Abstract: Grain depth-of-cut, which is the predominant factor determining the surface morphology, grinding force, and subsurface damage, has a significant impact on the surface quality of the finished part made of hard and brittle materials. When the existing analytical models are used to predict the gain depth-of-cut in ultra-precision grinding process of silicon wafer, the results obtained become unreasonable due to an extremely shallow grain depth-of-cut, which is inconsistent with the theory of the contact mechanics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…After that, wafer rotational speed was 121 r/min and the grinding wheel rotational speed were 2389 and 2409 r/min, respectively. In all experiments, the wheel infeed rate was 20 μm/min and the spark out time was 5 s. According to equation (22) and the research of Lin et al., 17 the value of δ is about 2 μm. It can be seen that the results of the experiments are consistent with the simulation, as shown in Figure 8.…”
Section: Experimental Verificationmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, wafer rotational speed was 121 r/min and the grinding wheel rotational speed were 2389 and 2409 r/min, respectively. In all experiments, the wheel infeed rate was 20 μm/min and the spark out time was 5 s. According to equation (22) and the research of Lin et al., 17 the value of δ is about 2 μm. It can be seen that the results of the experiments are consistent with the simulation, as shown in Figure 8.…”
Section: Experimental Verificationmentioning
confidence: 99%
“…According to researches of Lin et al. 17 and Young et al., 18 the maximum cutting depth of single abrasive grain is where d g is the cutting depth of single abrasive grain.…”
Section: Modelling Of Grinding Marks In the Bgwormentioning
confidence: 99%
“…1, most of the research on grinding considers grit tip radius to be equivalent to an imaginary spheroidal shape radius of the grit and assumes rigid-plastic material while revealing the effect of the grinding process and wheel parameters on average attainable depth-of-cut [8][9]. Earlier, Zhou et al [7] proposed a novel model of ultra-fine rotational grinding incorporating elastic-plastic response of the material and grit tip radius by adding two coefficients relating to material's elastic recovery and grit tip radius respectively. Their results show that the simplified assumption of assuming the grit tip radius as equal to the average grit radius becomes unreasonable in ultra-fine grinding.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the past, the concept of machining brittle materials in the ductile-mode such that the material removal occurs by virtue of plastic deformation as opposed to fracture has been well demonstrated in materials ranging from germanium, silicon and silicon carbide [4][5]. For this reason, various theoretical models are proposed aimed at optimisation of the rotational grinding process [6][7]. These models have shown that the quality of the finish depends on grinding parameters, grinding wheel topography, and stability of the tool-workpiece contact (chatter, vibrations etc.).…”
Section: Introductionmentioning
confidence: 99%
“…e methodology validated and provided a detailed information on grinding forces which was not addressed by the previous models. Lin et al [26] proposed a model of surface roughness by analyzing the grit depth of cut model in ultrafine rotational grinding. e results showed that the chip formation, the cutting tip radius, and the effective number of grains have to be considered for grit depth of cut prediction.…”
Section: Introductionmentioning
confidence: 99%